Risk perception of coronavirus disease 2019 and career adaptability among college students: the mediating effect of hope and sense of mastery - Ding, Yadong; Li, Jing (Frontiers in Psychology, 2023)
The Coronavirus Disease 2019 (COVID-19) pandemic has not only caused widespread economic recession but also had a serious negative impact on the employment of college students. However, little is known about the relationship and mechanisms between the risk perception of COVID-19 and career adaptability. This study aimed to examine whether the risk perception of COVID-19 is associated with career adaptability directly and indirectly through hope and a sense of mastery in college students. A questionnaire survey was conducted among 594 Chinese college students aged 16 to 25, who completed assessments on risk perception of COVID-19, career adaptability, hope, and sense of mastery. The results showed that susceptibility was negatively associated with career confidence, control, and curiosity; moreover, susceptibility indirectly affected career adaptability (including concern, confidence, control, and curiosity) through the sense of mastery; uncontrollable indirectly affected career concern through hope; and uncontrollable indirectly affected career adaptability (including concern, confidence, control, and curiosity) through hope and the sense of mastery. The findings emphasize the role of hope and a sense of mastery in the career adaptability of college students and reveal the necessity of improving hope and a sense of mastery to promote college students' career development. “Implications and limitations are discussed”.